PRETREATMENT OF LIGNOCELLULOSIC BIOMASS FOR ENZYMATIC HYDROLYSIS - Doan Thai Hoa; Tran Dinh Man; Ngo Viet Hau (ASEAN Journal on Science and Technology for Development, 2008)
The cost of raw materials continues to be a limiting factor in the production of bio-ethanol from traditional raw materials, such as sugar and starch. At the same time, there are large amount of agricultural residues as well as industrial wastes that are of low or negative value (due to costs of current effluent disposal methods). Dilute sulfuric acid pretreatment of elephant grass and wood residues for the enzymatic hydrolysis of cellulose has been investigated in this study.    Elephant grass (agricultural residue) and sawdust (Pulp and Paper Industry waste) with a small particulate size were treated using different dilute sulfuric acid concentrations at a temperature  of 140-170°C within 0.5-3 hours. The appropriate pretreatment conditions give the highest yield of soluble saccharides and total reducing sugars.